(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
In the present investigation, a combination of Eudragit L 30 D 55 and ethyl cellulose are used as enteric materials in a spray dried form to constitute the barrier layer for compression coating of directly compressed PSS core tablets. The study also includes analysis of the effect of Eudragit L 30 D 55 and ethyl cellulose and their optimisation using an extreme vertices design. Dissolution profile of compression coated tablets was best fitted to zero order and first order dissolution models. Mechanism of drug release was found to be Super case - II transport in all the batches as evidenced from the release exponent values of the Korsmeyer Peppas model. Mixture regression equations have indicated that Eudragit L 30 D 55 has more contribution towards the delayed drug release pattern, because it controls drug release below pH 6 in the acidic medium. Normal probability plots supported the accuracy of the chosen mixture design model for studying the effect of independent mixture variables, and had also shown that the residual values of response variables were minimal. Press coated tablets prepared using these optimised ratios of two mixture components have shown no statistical significant difference between their predicted and observed values of response variables as evidenced from the paired t-test (p-value > 0.2 in all the cases).